(3GdCLhHI GdeMQQI dCSFdI GdHQQIs - (3Ydj Hf eMeO Hf YHO GdQMef Hf Ydj, CHh GdEQTGO, fhQ GdOjf GdCLghQj,J (B1066 (3g` s
(3ChdgG (B:s
(3bO SCdJ faYc Gddg HGdYde Yf eSGFd hGfG CPcQ eG jJYdb Hcd Ydi Lg GdGNJUGQ s
(3BNQgG (B:s
(3Yde GdbQGAGJ hGdMOjK ELGRI HgeG hHLejY eG jLhR dg hYfg QhGjJg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B13 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B207s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B27s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg eGdc (B110) s
Keywords: (3Gdabg GdeGdcjs